Crustal Structure of Palmer Deep (West Coast of The Antarctic Peninsula) by Geophysical Data - V. D. Solovyov; V. G. Bakhmutov; I. N. Korchagin; S. P. Levashov (Ukrainian Antarctic Journal, 2009)
The Ukrainian Antarctic expeditions acquired new geoelectrical data ('short-impulse electromagnetic field formation' – FSPEF, and 'vertical electric-resonance sounding' – VERS) along profiles across Drake Passage and continental shelf of Antarctic Peninsula. The electromagnetic experiments yielded new data set with unique information about the inner structure and new values of the depth of the Moho discontinuity of West Antarctica region. Deep crustal heterogeneities of the Palmer Deep Basin that were obtained from the VERS- profiles data could be connected with processes of tectonic transformations of the Antarctic Peninsula shelf structures. Possibly, the conformities of continental shelf glacial streams may be explained exactly by a tectonic factor of recent geological past. New information about sediment distribution and inner crustal structure has an important value for searching and prospecting the hydrocarbon deposits of Palmer Deep region